Effect of pelvic floor rehabilitation technique in preventing the postpartum pelvic floor dysfunction - Shi-Qiong Li (Journal of Hainan Medical University, 2017)
Objective: To explore the effect of pelvic floor rehabilitation technique in preventing the postpartum pelvic floor dysfunction and on the sexual life quality. Methods: A total of 286 puerpera with pelvic floor dysfunction who were admitted in our hospital from May, 2014 to May, 2015 42 d after delivery were included in the study, and randomized into the treatment group and the control group with 143 cases in each group. After guidance, the puerpera in the control group were given pelvic floor muscle training by themselves at home. On this basis, the puerpera in the treatment group were treated by the pelvic floor rehabilitation apparatus. The puerpera in the two groups were treated for 4 weeks. The pelvic floor function before treatment, 6 months and 1 year after delivery was detected. The color Doppler ultrasound apparatus was used to detect BSD, PUVA, UVJ-M, and BND 3 months after delivery. Results: BND, PUVA-R, PUVA-S, and UVJ-M 3 months after delivery in the treatment groups were significantly lower than those in the control group, while BSD-S was significantly higher than that in the control group. The improvement of type I and II muscle fiber fatigue (%), POP-Q degree, AP indication point (cm), and vaginal dynamic pressure (cmH2O) was significantly superior to that in the control group. The comparison of pelvic floor muscle strength classification before treatment between the two groups was not statistically significant. After treatment, the pelvic floor muscle in the two groups was significantly strengthened, and the proportion of V grade patients was significantly increased when compared with before treatment. Conclusions: The postpartum early pelvic floor rehabilitation technique can effectively enhance the pelvic floor function, and prevent the postpartum pelvic floor dysfunction, with an accurate efficacy; therefore, it deserves to be widely recommended in the clinic.